Developing Gamification Media-Based on RADEC Model Using Genially to Enhance Elementary Students Reading Comprehension of Narrative Texts - Kholisna, Arin; Sukasih, Sri (Journal of Integrated Elementary Education, 2025)
This study aimed to create gamified learning media based on the RADEC model, using Genially to boost fifth-grade students' reading comprehension of narrative texts. Following a Research and Development (R&D) approach within the ADDIE framework, the research adhered to a structured process: analyze, design, develop, implement, and evaluate. The analysis phase unveiled key challenges, such as students' difficulties in identifying main ideas and their lack of engagement with narrative texts, highlighting the necessity for innovative, technology-driven learning tools. In the design phase, engaging gamified media rooted in the RADEC model was crafted on Genially.com, incorporating interactive and visually appealing activities aligned with the RADEC steps (Read, Answer, Discuss, Explain, Create). The development phase involved expert and educator reviews of the media, which yielded a feasibility rating exceeding 90% after refinements were made based on their feedback. During the implementation phase, both small- and large-group trials were conducted, leading to significant improvements in reading comprehension. Pretest-posttest comparisons, bolstered by N-Gain scores, classified the media as "quite effective," with paired sample t-tests confirming statistically significant progress. The study also highlighted high satisfaction levels among teachers and students, who lauded the media for its engaging and effective approach to enhancing comprehension. Ultimately, the study concluded that gamified media, when combined with the RADEC model, effectively boosts cognitive and motivational outcomes, demonstrating its value in real-world classrooms. While the research centered on narrative texts, it emphasizes the potential of interactive technology to cultivate meaningful and enjoyable learning experiences. Future studies should further explore this approach with various text types to enhance digital literacy in 21st-century education.